The Study of Religion and the Training of Muslim Clergy in Europe : Academic and Religious Freedom in the 21st Century - Drees, Willem; Koningsveld, Pieter Sjoerd (Leiden University Press, 2007)
Religious scholarship can be offensive to believers, as conflicts from the time of Galileo and Spinoza to the recent critique of Danish religious scholars in the wake of the infamous Muhammad cartoons have shown. Studies of this type of scholarship have been appropriated by believers as a means of reinventing their own identities - as the training of twentieth-century Muslim clergy demonstrates. This volume offers a unique collection of training materials from European Muslim clergy since the 1940s - including Third Reich reports on debriefing imams, surveillance files on Muslim activists, and information on Bosnian clergy and their training centres - as well as an exploration of religion and academic freedom in general, accompanied by appendices in both Arabic and English.
Spanningen tussen academische en religieuze vrijheid kunnen grote maatschappelijke gevolgen hebben. Te denken valt aan de onlusten ten gevolge van de Deense cartoons, de gevolgen van '11 september' voor wetenschappelijk onderzoek, en de juridische strijd over evolutie en 'Intelligent Design'. Er zijn in onze tijd echter ook positieve ontwikkelingen. Belangrijk is dat in Europa, op verschillende manieren, gewerkt wordt aan opleidingen voor islamitische geestelijke leiders. Dit zijn opleidingen die niet geïsoleerd zijn maar verbonden met de universitaire wereld. Dit boek biedt een eerste studie van de wetenschappelijke training van islamitische geestelijken in Europa in samenhang met de bestudering van religie en academische vrijheid.
English
Keywords: Religion & beliefs; islam; imam; religie; training; religion; muslim clergy; Academic freedom